Cartas invitación, prácticas ilegales del Servicio de Administración Tributaria - Vieyra Sánchez, Gerardo (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The Tax Administration Service, being a decentralized body of the Secretary of Hacienda and Public Credit, carries out administrative acts that allow it to collect the necessary revenues to cover the public expenditure of the Federation. Thus, the tax authorities have various powers established in the legislation that allow them to fulfill their main function, the collection of taxes. In this regard, invitation letters issued and sent by the Tax Administration Service, are configured as an act of the tax authority with the intention of inviting the taxpayer to a self-correction provided that it has been warned, for the consideration of the authority, the possible existence of irregularities in the fulfillment of tax obligations borne by taxpayers. In addition, these invitation letters have the characteristic of being optional, that is, they are acts that the taxpayers can abide by or not since they are not configured as definitive acts of the tax authority. Thus, the jurisprudence of both the Supreme Court of Justice of the Nation and the Federal Court of Administrative Justice had considered that, due to the very optional nature of the invitation letters and that they do not constitute a final resolution of authority, no harm is done to the legal sphere of the taxpayer.

El Servicio de Administración Tributaria, al ser un órgano desconcentrado de la Secretaria de Hacienda y Crédito Público, lleva a cabo actos administrativos que le permiten recaudar los ingresos necesarios para cubrir el gasto público de la Federación. Así, las autoridades fiscales cuentan con diversas facultades establecidas en la legislación que les permiten cumplir con su principal función, la recaudación de impuestos. Al respecto, las cartas invitación emitidas y enviadas por el Servicio de Administración Tributaria, se configuran como un acto propio de la autoridad fiscal con la intención de invitar al contribuyente a una autocorrección siempre que se haya advertido, a consideración de la autoridad, la posible existencia de irregularidades en el cumplimiento de obligaciones fiscales a cargo de los contribuyentes. Además, estas cartas invitación tienen la característica de ser optativos, es decir, son actos que los contribuyentes pueden acatar o no ya que no se configuran como actos definitivos de la autoridad fiscal. Así, la jurisprudencia tanto de la Suprema Corte de Justicia de la Nación como del Tribunal Federal de Justicia Administrativa, han considerado que, por el propio carácter opcional de las cartas invitación y que las mismas no constituyen una resolución definitiva de autoridad, no se realiza un daño a la esfera jurídica del contribuyente.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2023-0106; Fisco; Contribuyentes; Prácticas ilegales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16398